Effects of Quinizarin and Five Synthesized Derivatives on Fifth Larval Instar Midgut Ecdysone 20-Monooxygenase Activity of the Tobacco Hornworm Manduca sexta - Drummond, Christopher A.; Molina, Maria Teresa; Taliansky, Sandra; Breidenbach, Carl R.; Fioravanti, Carmen F. (International Journal of Zoology, 2014)
The plant allelochemical, quinizarin (1,4-dihydroxy-9,10-anthraquinone), and five anthraquinones that were synthesized from quinizarin, namely, 1,4-anthraquinone; 2-hydroxy-1,4-anthraquinone; 2-methoxy-1,4-anthraquinone; 9-hydroxy-1,4-anthraquinone; and 9-methoxy-1,4-anthraquinone, were assessed as to their effects on the essential, P450-dependent ecdysone 20-monooxygenase system of the insect model Manduca sexta (tobacco hornworm). This steroid hydroxylase converts the arthropod molting hormone, ecdysone, to the physiologically required 20-hydroxyecdysone form. M. sexta fifth larval instar midgut homogenates were incubated with increasing concentrations (10−8 to 10−3 M) of each of the six anthraquinones followed by ecdysone 20-monooxygenase assessments using a radioenzymological assay. Four of the five anthraquinones exhibited I50’s of about 4×10-6 to 6×10-2 M. The most effective inhibitors were 2-methoxy-1,4-anthraquinone and 1,4-anthraquinone followed by 9-hydroxy-1,4 anthraquinone and 9-methoxy-1,4-anthraquinone. At lower concentrations the latter anthraquinone stimulated E20M activity. Quinizarin was less inhibitory and 2-hydroxy-1,4-anthraquinone was essentially without effect. Significantly, these studies make evident for the first time that anthraquinones can affect insect E20M activity, and thus insect endocrine regulation and development, and that a relationship between anthraquinone structure and effectiveness is apparent. These studies represent the first demonstrations of anthraquinones affecting any steroid hydroxylase system.